Evaluation measure of 3d volumetry of masseter hypertrophy: association with modalities of imaging - Antonione Santos Bezerra PINTO; Neiandro dos Santos GALVÃO; Jean de Pinho MENDES; Paulo Henrique Viana PINTO; Sérgio Lúcio Pereira de Castro LOPES; André Luiz Ferreira COSTA (Faculdade São Leopoldo Mandic, 2018)
Masseteric hypertrophy is a benign condition, asymptomatic and rare, characterized by the excessive development of the masseter muscle, which usually results in aesthetic complaints. The imaging exams for differential diagnosis of pathologies in the parotid-masseteric region is always recommended. This work aims the imaging characterization of masseteric hypertrophy through the report of two clinical cases combining different imaging modalities: panoramic radiography, magnetic resonance imaging, computed tomography, ultrasonography and 3D volumetry. Two male subjects with no family history of masseteric hypertrophy were referred to a diagnostic center in dentomaxillofacial radiology due to an increase in bilateral facial volume in the masseteric region. Images of the panoramic radiography showed an increase of the bilateral mandibular angle in both cases. Using computerized tomography, bilateral masseter muscle hypertrophy was demonstrated in the patients, and magnetic resonance scan and ultrasound examination were performed for better visualization and muscle measurement. 3D volumetry assessment of musculature showed as additional tool to evaluate the status of the masseter muscles in patients with Masseteric hypertrophy. Therefore, the association of imaging examinations allowed to perform the imaging characterization of masseteric hypertrophy with presence of bone exostosis.